Microsurgical versus Conventional Inguinal Varicocelectomy: A Systematic Review of Fertility Outcomes and Recurrence Risk - Bobby Aksanda Putra; Beny Levi Andreas Sibarani; Maeike Grestiana Sinaga (Jurnal Siti Rufaidah, 2025)
Infertility affects approximately 8–12% of couples worldwide, with male factors contributing to nearly half of all cases. Varicocelectomy, particularly the microsurgical subinguinal technique, is now considered the primary treatment that provides superior reproductive outcomes compared to conventional or laparoscopic approaches. To evaluate and compare fertility outcomes and recurrence risks between microsurgical and conventional inguinal varicocelectomy, based on recent evidence from 2020 to 2025. Methods A systematic review was conducted using databases including PubMed, Scopus, Cochrane, ScienceDirect, and Google Scholar. Out of 371 identified articles, 9 studies met the inclusion criteria. Results, most studies demonstrated that the microsurgical technique significantly improved sperm concentration, motility, and morphology, as well as higher natural pregnancy rates. The risks of hydrocele and recurrence were also markedly lower than those observed with laparoscopy. The average postoperative sperm count increased by 7.7 ± 4.5 million/mL (p< 0.001). Furthermore, the microsurgical subinguinal approach allows for more precise identification of arteries and lymphatic vessels, thereby minimizing vascular injury and facilitating faster recovery. Conclusion, the microsurgical subinguinal varicocelectomy has proven to be more effective and safer than conventional approaches. This technique significantly enhances semen parameters and pregnancy rates, while reducing the risk of hydrocele formation and recurrence.